Transparent thermal insulation ceramic aerogel materials for solar thermal conversion. Issue 20 (9th September 2022) - An, Lu; Li, Zheng; Guo, Zipeng; Hu, Yong; Huang, Yulong; Armstrong, Jason N.; Zhou, Chi; Ren, Shenqiang
Abstract : Transparent ceramic aerogel materials toward emerging energy-efficient solar thermal window technologies. Abstract : Thermal management in energy-efficient solar thermal energy conversion and transparent windows requires advanced materials with low thermal conductivity and high transparency, such as transparent silica aerogel materials. However, the large scatter domains in porous silica materials would deteriorate their optical transparency. Herein, we report transparent silica aerogels by controlling hydrolyzation and meanwhile silylation modification to enhance the integrity of the microstructure under ambient pressure drying. The transparent silica aerogel materials show a broad-spectrum transparency of 70% from 400 nm and 800 nm, showing promising applications in transparent windows and solar thermal energy conversion systems. The scalability for transparent windows could be achieved with a composite material by incorporating transparent polymeric materials. The solar receiver coupled with a transparent silica aerogel could reach 122 °C within 12 min at a solar irradiance of 1 Sun, ∼200% higher than that in the ambient atmosphere. The engineered structure of the transparent porous silica backbone provides a pathway for solar thermal systems and transparent window applications.